P-170 The EAPC core domains for dementia – benchmarking admiral nursing. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Dening, Karen Harrison; Scates, Caroline
Abstract : There are over 850 000 people living with dementia in the UK, with numbers projected to triple by 2050. Dementia prevalence increases with age, affecting 6% of those aged 75–79 years and a third of people over the age of 95 (Knapp & Privette, 2007). Increasing numbers of people will die with dementia and in 2015 dementia became the commonest cause of death in men and women over the age of 80 years (Office for National Statistics, 2017). Deaths due to dementia will increase to around 220, 000 deaths per year by 2040 leading to an increased need for palliative care (Etkind, Bone, Gomes et al ., 2017). Identifying when people with dementia are reaching the end of their life can be challenging and some studies have attempted to identify prognostic indicators to guide clinicians to adopt a palliative care approach. However, these tools are more reliable at identifying people with dementia at low risk of dying rather than those at higher risk of death (van der Steen, Ooms, van der Wal et al ., 2005). So what does palliative care for people with dementia 'look like'? Definitions of palliative care share a common philosophy, which is an holistic approach, valuing autonomy of patients and families, focussing on dignity, collaborative relationships between healthcare professionals, patients and their families, good communication, and a central goal to maintain quality of life. The European Association for Palliative Care (EAPC) surveyed experts in the field using a Delphi process and published a consensus statement defining the principles of practice for palliative care in dementia (van der Steen, Radbruch, Hertogh et al ., 2014). Around this time Dementia UK developed its 'hospice model' of Admiral Nursing, of which services are growing. This paper will describe benchmarking of the Admiral Nurse palliative care approach against the domains and recommendations as set out in the EAPC white paper.